Development of Module Early Childhood Education Based on Panca Amal Al-Washliyah to Improve Teacher's Pedagogic Competence in RA Al-Washliyah Kisaran Kabupaten Asahan Sumatera Utara - Mhd Habibu Rahman; Maemonah Maemonah (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2019)
The purpose of this study was to develop a PAUD module based on the Panca Amal Al-Washliyah, and to find out its effectiveness in improving teacher pedagogical competence at RA Al-Washliyah Kisaran. This type of research is research and development (R & D). The development process includes planning, design, and development. Product validation was carried out by media experts, material experts, Al-Washliyah administrators, and colleagues. The results of the study indicate that the product developed is feasible to be used as an independent learning media that can be used by educators. This is based on the overall assessment score of the validator, namely media experts, material experts, Al-Washliyah administrators, and colleagues who have been converted in interval data to produce positive gradients. Furthermore, based on the results of the pretest with scores of 12.25 and posttest of 25.50, there was an increase in knowledge of pedagogic competencies of 13.25 with a standard gain of 0.76 which was in the "high" category. Observations on the pedagogical competence activities of teachers showed that 93% were in the "very high" category. Based on these results, the modules developed were effective in improving teacher pedagogical competencies.Keywords: Modules; PAUD Based on Five Charities Al-Washliyah; Pedagogic Competence. AbstrakTujuan dari penelitian ini adalah untuk mengembangkan modul PAUD Berbasis Panca Amal Al-Washliyah, serta mengetahui efektivitasnya dalam meningkatkan kompetensi pedagogik guru di RA Al-Washliyah Kisaran. Jenis penelitian ini adalah research and depelovment (R&D). Proses pengembangan meliputi perencanaan, desain dan pengembangan. Validasi produk dilakukan oleh ahli media, ahli materi, pengurus Al-Washliyah, dan teman sejawat. Hasil penelitian menunjukkan bahwa produk yang dikembangkan layak untuk digunakan sebagai media pembelajaran mandiri yang dapat digunakan oleh pendidik. Hal ini didasarkan pada skor penilaian keseluruhan validator yaitu ahli media, ahli materi, pengurus Al-Washliyah, dan teman sejawat yang telah dikonversi dalam data interval menghasilkan gradiasi positif. Selanjutnya berdasarkan hasil pretest dengan nilai 12,25 dan posttest sejumlah 25,50 menunjukkan adanya peningkatan pengetahuan kompetensi pedagogik sejumlah 13,25 dengan gain standar 0,76 yang berada pada kategori “tinggi”. Observasi terhadap aktivitas kompetensi pedagogik guru menunjukkan dalam persentase 93% yang berada pada kategori “sangat tinggi”. Berdasarkan hasil tersebut menunjukkan modul yang dikembangkan efektif dalam meningkatkan kompetensi pedagogik guru. Kata Kunci: Modul; PAUD Berbasis Panca Amal Al-Washliyah; Kompetensi Pedagogik.